A Cost Reduced Variant of Epi-Genotyping by Sequencing for Studying DNA Methylation in Non-model Organisms - Werner, Olaf; Prudencio, Ángela S.; de la Cruz-Martínez, Elena; Nieto-Lugilde, Marta; Martínez-Gómez, Pedro; Ros, Rosa M. (Frontiers in Plant Science, 2020)
In this paper, we present a modification of the epiGBS protocol that requires the use of only one hemimethylated P2 (common) adapter, which is combined with unmethylated barcoded adapters. Reference-free reduced representation bisulfite sequencing makes it possible to study the DNA methylation of a high number of individuals in natural populations of non-model organisms. Unlike other comparable methods like epiGBS and BsRADseq, which require the use of a higher number of methylated DNA oligos with a significant cost (especially for small labs and first pilot studies), in our protocol, the unmethylated cytosines of one chain of the barcoded adapter are replaced by methylated cytosines using nick translation with methylated cytosines in dNTP solution. The basic version of our technique uses only one restriction enzyme, and as a result, genomic fragments are integrated into two orientations with respect to the adapter sequences. Comparing the sequences of two chain orientations makes it possible to reconstruct the original sequence before bisulfite treatment with the help of standard software and newly developed software written in C and described here. We provide a proof of concept via data obtained from almond (Prunus dulcis). Example data and a detailed description of the complete software pipeline starting from the raw reads up until the final differentially methylated cytosines are given in supplementary files. The .adapter design showed in this paper should allow the use of a two restriction enzyme approach with minor changes in software parameters.